Metode Perekrutan Karyawan UKM Melalui Wawancara dengan Pendekatan Visi, Misi, Dan Nilai Perusahaan - Adiguna Sasama Wahyu Utama; Anang Widigdyo; Anna Widayani (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2023)
SMEs or Micro, Small and Medium Enterprises play a very important role for the Indonesian economy. In the Indonesian economy, SMEs are the business group with the largest percentage. However, of the much assistance and attention provided by the government to SMEs, very little has been discussed regarding the Human Resources (HR) involved as employees in SMEs. so that SMEs can have a competitive advantage over their larger competitors, SMEs need to be involved in effective and efficient HR management practices, one of which is in terms of recruiting employees. One method of recruiting employees that is simple and can be applied easily is an interview. However, in conducting interviews, SME actors cannot ask questions without a clear framework because it will waste time and energy. Interview questions can be developed based on the three categories that most influence employee engagement, namely organizational factors, job factors, and individual factors.